Analysis of breast MRI performed on patients with axillary nodal metastasis and negative mammogram and ultrasound - Pichayakul, Pakpawee; Hansakul, Palita (Chulalongkorn Medical Journal, 2024)
Background: Occult breast cancer is a rare type of breast cancer which magnetic resonance imaging (MRI) has an immense role to confirm diagnosis and disclose non-demonstrable finding on initial modality. Objectives: To analyge breast MRI findings in patients with axillary nodal metastasis and negative mammo gram and ultrasound and retrospectively review the initial mammography and second-look ultrasound. Methods: From January 2010 to January 2023, women who diagnosed occult breast cancer by presenting metastatic axillary lymph node on pathological report with negative mammography and ultrasonography, underwent breast MRI to identify occult breast carcinoma. Their breast MRI were retrospectively reviewed. The imaging findings on breast MRI were collected and confirmed associated findings on second-look ultrasound and initial mammograms. Results: There were 12 patients diagnosed with occult breast cancer. Breast MRI detected primary cancer in 4 of 12 (33.0%) patients. In two out of four patients, the MR-correlated second-look ultrasound localized lesions that were not detected on the initial exam. One case demonstrated MR-correlated finding on retrospective mammography and the other case was detected as suspicious lesions on both second-look ultrasound and retrospective mammography. Conclusion: Breast MRI is an important modality for investigation of occult breast cancer. MR-correlated second-look ultrasound and retrospective mammography localized lesions from the prior negative reports are valuable learning points to improve detection and interpretation skills.